PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. BPR Arta Utama Pekalongan) - Robertus Gita; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to analyze further the effect of transformational leadership style,employee motivation, and organizational culture on employee performance. In this study, theresearcher uses of transformational leadership style, work motivation, and organizational cultureas an independent variables and employee performance as the dependent variable.Methods of data collection in the research that is used is a questionnaire with a sample of 57permanent employees of PT. BPR Arta Utama Pekalongan (consisting of a central office and fourbranch offices), in which the research is using a sample of census or using the entire population ofemployees of PT. BPR Arta Utama. Methods of data analysis used in this research is multiplelinear regression analysis.Based on the multiple linear regression that is performed to produce transformational leadershipstyle, it has a positive and significant impacts on employee performance. Meanwhile, workmotivation and organizational culture do not affect the performance of employee.Keywords : Transformational leadership style, work motivation, organizationalculture, and employee performance.